Aquatic insects as bio-indicators of water quality – a study on Sungai Kawal, Johor National Park of Endau-Rompin, Peninsular Malaysia - N. I. R., Yap; K. R., Kamarudin; Rehan, A. M.; N. S., Badrulhisham; M. Z., Zakaria; J., Kemalok (2020)
Biological indicator species or bio-indicators are sensitive to specific environmental factors so that changes in their environment will be reflected by their incidence or abundance. In fact, aquatic insects of freshwater river and stream ecosystems have been widely used as bioindicators to examine the species-habitat relationship with regard to the water quality of the habitat. Therefore, this study attempted to determine species richness of aquatic insects in Sungai Kawal, Johor National Park of Endau-Rompin (TNJER), Mersing, Johor, Malaysia; to identify traditional knowledge (TK) used by Jakun tribe in Kampung Peta, TNJER for maintaining rivers and streams at good level; and then to correlate the relationship between the scientific perspective and TK perspective. Aquatic insects were collected and sampled by using kick sampling technique and D-framed net. Throughout the study, a total of 618 individuals consisting of 23 families belonging to seven orders of aquatic insects were reported. The documentation of TK was done by interviewing 10 total respondents of the Jakun tribe in Kampung Peta. Physical features of Sungai Kawal were also recorded during sampling. The correlation between the scientific perspective and TK perspective regarding how the ecosystem maintenance by the Jakun tribe has contributed to an excellent habitat for the aquatic insects to breed and multiply. The number of species recorded indicated the good status of water quality of Sungai Kawal based on science and then supported by TK of the Jakun tribe of Kampung Peta. Furthermore, the findings also suggested a good correlation between the scientific perspective and TK perspective, and the significant contribution of TK of the Jakun tribe to the management of natural resources.